The effect of corporate social responsibility, profitability, independent commissioners, sales growth and capital intensity on tax avoidance - Faradisty, Astrid; Hariyani, Eka; Wiguna, Meilda (Journal of Contemporary Accounting, 2019)
This study aims to examine and determine the effect of corporate social responsibility, profitability, independent commissioner and sales growth on tax avoidance.The sampling method used in this study was the purposive sampling method for the period 2015-2017 in the Indonesian stock exchange at 154 manufacturing companies and 32 samples with multiple regression analysis. The results shows that the variables of corporate social responsibility, independent commissioner, and sales growth variables have an effect on tax avoidance. On the other hand, the variables of profitability and capital intensity does not affect tax avoidance. For future studies it is necessary to add an independent variable to see its effect on tax avoidance and to compare it with samples in other sectors outside manufacturing companies.